Situating and Constructing Diversity in Semi-Structured Interviews - McIntosh, Michele J.; Morse, Janice M. (Global qualitative nursing research, 2015)
Although semi-structured interviews (SSIs) are used extensively in research, scant attention is given to their diversity, underlying assumptions, construction, and broad applications to qualitative and mixed-method research. In this three-part article, we discuss the following: (a) how the SSI is situated historically including its evolution and diversification, (b) the principles of constructing SSIs, and (c) how SSIs are utilized as a stand-alone research method, and as strategy within a mixed-method design.